2017
DOI: 10.1016/j.msea.2016.11.066
|View full text |Cite
|
Sign up to set email alerts
|

High temperature thermal stability of nanocrystalline 316L stainless steel processed by high-pressure torsion

Abstract: Differential scanning calorimetry (DSC) was used to study the thermal stability of the microstructure and the phase composition in nanocrystalline 316L stainless steel processed by high-pressure torsion (HPT) for ¼ and 10 turns. The DSC thermograms showed two characteristic peaks which were investigated by examining the dislocation densities, grain sizes and phase compositions after annealing at different temperatures. The first DSC peak was exothermic and was related to recovery of the dislocation structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 40 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…The thickness and the diameter of the HPT-processed disks were ~0.75 mm and ~10 mm, respectively. In former studies, the microstructure and the phase composition evolution during HPT processing and subsequent annealing were investigated in detail [2,5]. Differential scanning calorimetry (DSC) revealed that between ~590 and ~740 K there was only a recovery in the microstructure whereas between ~740 and ~1000 K recovery, grain growth and an almost complete reversion of α'-martensite to γ-austenite was also detected [5].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The thickness and the diameter of the HPT-processed disks were ~0.75 mm and ~10 mm, respectively. In former studies, the microstructure and the phase composition evolution during HPT processing and subsequent annealing were investigated in detail [2,5]. Differential scanning calorimetry (DSC) revealed that between ~590 and ~740 K there was only a recovery in the microstructure whereas between ~740 and ~1000 K recovery, grain growth and an almost complete reversion of α'-martensite to γ-austenite was also detected [5].…”
Section: Methodsmentioning
confidence: 99%
“…In former studies, the microstructure and the phase composition evolution during HPT processing and subsequent annealing were investigated in detail [2,5]. Differential scanning calorimetry (DSC) revealed that between ~590 and ~740 K there was only a recovery in the microstructure whereas between ~740 and ~1000 K recovery, grain growth and an almost complete reversion of α'-martensite to γ-austenite was also detected [5]. Therefore, in this study the tensile performance was investigated for the samples annealed to the two characteristic temperatures of the DSC thermograms, i.e., to ~740 and ~1000 K. Small specimens were cut from the regions between the half-radius and the periphery of the HPT disks and these samples were heated in the calorimeter to ~740 and ~1000 K at a heating rate of 20 K/min and then quenched to RT at ~300 K/min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, many papers have been devoted to understanding these phenomena in microcrystalline [1,2], and recently in nanocrystalline, materials [3][4][5]. During the annealing of nanocrystalline materials produced by severe plastic deformation (SPD) techniques, one can observe typical processes of recovery, recrystallization and grain growth, but they follow a different course than in materials deformed by conventional techniques [6][7][8].…”
Section: Introductionmentioning
confidence: 99%